2022
DOI: 10.1002/adfm.202200018
|View full text |Cite
|
Sign up to set email alerts
|

Activating Energy Transfer Tunnels by Tuning Local Electronegativity of Conjugated Polymeric Backbone for High‐Efficiency OLEDs with Low Efficiency Roll‐Off

Abstract: Thermally activated delayed fluorescence (TADF) conjugated polymers are attractive for display and illumination applications owing to their excellent device performance and convenient device fabrication. However, conjugated polymers frequently encounter insufficient energy transfer from hosts to TADF units, lowering device performance. Herein, a strategy for improving light-emitting performances through adjusting the local electronegativity of the polymeric backbones by inserting electron-withdrawing atoms and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…Meanwhile, the intersystem crossing process of the excited states can probably be tuned and thus enhance spin-orbit coupling (SOC) between singlet and triplet states and light-emitting efficiency according to Fermi's golden rule [38][39][40][41] . In practice, modulating the energy levels of excited states to enhance the efficiency has been implemented in blue-green emitters [42][43][44][45] . There are, however, few reports on the regulation of intersystem crossing processes of orangered light emitters.…”
mentioning
confidence: 99%
“…Meanwhile, the intersystem crossing process of the excited states can probably be tuned and thus enhance spin-orbit coupling (SOC) between singlet and triplet states and light-emitting efficiency according to Fermi's golden rule [38][39][40][41] . In practice, modulating the energy levels of excited states to enhance the efficiency has been implemented in blue-green emitters [42][43][44][45] . There are, however, few reports on the regulation of intersystem crossing processes of orangered light emitters.…”
mentioning
confidence: 99%
“…pBP-PTZ and pBP-PXZ with sulfurand oxygen-containing donors in the polymeric backbones, respectively, are investigated. 4 The electron-withdrawing atoms with a stronger electronegativity have a significant impact on the electronic structures of polymeric emitters. As the electro- negativity of the embedded atoms increases, the delocalization range of HOMO continuously narrows.…”
Section: Of the Conjugated Polymeric Backbones By Copolymerizing The ...mentioning
confidence: 99%
“…Besides, our prior research has demonstrated that the energy transfer process from hosts to TADF units would be enhanced through adjusting the local electronegativity of the polymeric backbones by inserting electron-withdrawing atoms. Strongly electronegative atoms located on the branched chains can activate the advantageous tunnels of hole transportation from the hosts to TADF cores, which are beneficial in realizing further optimization of the efficiency roll-off . Under a rational regulation of TADF unit ratio, the HCP with 7.5% TADF cores (HCP-7.5%) performs the best device performance.…”
Section: Introductionmentioning
confidence: 99%
“…Strongly electronegative atoms located on the branched chains can activate the advantageous tunnels of hole transportation from the hosts to TADF cores, which are beneficial in realizing further optimization of the efficiency rolloff. 27 Under a rational regulation of TADF unit ratio, the HCP with 7.5% TADF cores (HCP-7.5%) performs the best device performance. The corresponding nondoped PLED device achieves a red emission with an EQE max of 8.39% and exhibits no roll-off when the luminance is less than 100 cd/m 2 and only 3.3% decrease at 500 cd/m 2 .…”
Section: ■ Introductionmentioning
confidence: 99%